Pengaruh Penetapan Harga Dan Kualitas Pelayanan PT. Ciomas Adisatwa Terhadap Kepuasan Mitra Kerja Di Kecamatan Tongas Kabupaten Probolinggo - Rizki, Miftahur; Farida, Eka; Millaningtyas, Restu (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research was conducted to determine the effect of pricing and service quality on the satisfaction of PT Ciomas Adisatwa partners in Tongas sub-district, Probolinggo regency. The type of research used is quantitative research. The population in the study were work partners who joined PT. Ciomas Adisatwa, Tongas District Probolinggo Regency for the period from August 2023 to December 2023. The approach method used is purposive sampling with the distribution of questionnaires to 33 respondents. Data processing using SPSS analysis mats. In the results of this study, it can be concluded that pricing and service quality simultaneously affect the satisfaction of PT Ciomas Adisatwa partners in Tongas sub-district, Probolinggo regency. Keywords: Service Quality, Pricing, Work Partner Satisfaction.